Pengaruh Model Pembelajaran Inkuiri Berbasis Website Terhadap Kemampuan Kognitif Siswa Kelas X Kompetensi Keahlian Multimedia Pada Mata Pelajaran Komputer dan Jaringan Dasar di SMK Negeri 2 Buduran - Karina Maulidiyah; Fitria Nur Hasanah (Proceedings of The ICECRS, 2019)
This study was aimed to determine if there is influence of the website-based inquiry learning model on cognitive abilities of class and how much the influence of the website-based inquiry learning model has on the cognitive abilities of class X multimedia students expertise competencies in computer subjects and basic networks in SMK Negeri 2 Buduran. This research method used quantitative research methods Quasi Experimental Design with the design of "Nonequivalent Control Group Pretest-Posttest Design". The population in this study were 108 students of X Multimedia class 72 students as sample consisting of 36 X-TI3 students as the control class and 36 X-TI2 students as the experimental class. The instrument used in this study was the learning achievement test, where there as a pretest (which has not been treated) and posttest (which has been treated). The data obtained were then analyzed using the t-test with t count = (14,978)> t table (1,667) at a significant level of 5%. If the t count is outside the acceptance of H0, then H0 is rejected and H1 is accepted. After knowing the prettest and posttest results that have been tested to students to find out whether there is an influence or not it is done by using the analysis of N-Gain test data. From the results of the N-Gain test calculation produces 0.61 which is included in the Medium category. From the results of the study, it can be concluded that the inquiry learning model has a moderate effect on the cognitive abilities of class X multimedia students expertise competencies in computer subjects and basic networks in SMK Negeri 2 Buduran.